2009 IEEE International Conference on Acoustics, Speech and Signal Processing 2009
DOI: 10.1109/icassp.2009.4959621
|View full text |Cite
|
Sign up to set email alerts
|

Dictionary learning for the sparse modelling of atrial fibrillation in ECG signals

Abstract: We propose a new method for ventricular cancellation and atrial modelling in the ECG of patients suffering from atrial fibrillation. Our method is based on dictionary learning. It extends both the average beat subtraction and the sparse source separation approaches. Experiments on synthetic data show that this method can almost completely suppress the ventricular activity, but it generates some artifacts. Contrary to other ventricular cancellations methods, our approach also learns a model for the atrial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…2. Sparse representations have been proposed by [13] for ECG source separation problems, which motivated the utilization of the proposed approach for Arrhythmia detection: given an ECG signal that contains mostly normal heartbeats, the key idea is to decompose the signal into all possible -samples windows (on the order of 1 second duration) and train a dictionary that will provide a sparse representation for these windows. Note that due to the multiplicity and periodicity of normal heartbeats, their corresponding windows are highly repetitive, and constitute the majority among all windows.…”
Section: Arrhythmia Detection In Ecg Signalsmentioning
confidence: 99%
“…2. Sparse representations have been proposed by [13] for ECG source separation problems, which motivated the utilization of the proposed approach for Arrhythmia detection: given an ECG signal that contains mostly normal heartbeats, the key idea is to decompose the signal into all possible -samples windows (on the order of 1 second duration) and train a dictionary that will provide a sparse representation for these windows. Note that due to the multiplicity and periodicity of normal heartbeats, their corresponding windows are highly repetitive, and constitute the majority among all windows.…”
Section: Arrhythmia Detection In Ecg Signalsmentioning
confidence: 99%
“…Conversely, a customized dictionary, built from real-world signals, will provide a better performance in terms of the reconstruction error obtained for a given level of sparsity. Consequently, several on-line dictionary learning approaches have also been applied, both in the context of sparse inference and compressed sensing (CS), to ECG signals: the K-SVD algorithm in [15], the shift-invariant K-SVD in [16], and the method of optimal directions in [17]. Unfortunately, all these methods have a high computational cost (due to their need to iterate between the dictionary learning and sparse approximation stages) and lead to dictionaries whose atoms do not correspond to real-world signals (thus reducing the interpretability of the sparse model, as well as the ability to easily locate the relevant waveforms).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by their work, dictionary-learning methods have been proposed in biomedical signal such as ECG, EEG and EMG. While most of the existing works focus on ECG [13,14] signals, there are fewer studies reported using EEG signals. Moreover, event-related EEG signals used in Brain-Computer-Interface (BCI) tend to be the potential candidate signals.…”
Section: Introductionmentioning
confidence: 99%